Single-Phase Wireless Electric Vehicle Charger Using EF2 Inverter - Soumya Ranjan Meher; Rajeev Kumar Singh (International Transactions on Electrical Energy Systems)
This paper proposes a wireless battery charger topology for electric vehicle (EV) application that can be installed in public charging infrastructure as well as in home premises. The proposed topology can maintain constant current as well as constant voltage at the battery terminal and simultaneously can maintain near unity power factor at the input side using power factor correction (PFC) operation and thus satisfy all the criteria of a standard EV charger. The heart of the wireless power transfer (WPT) scheme is a high-frequency (HF) inverter. In this work, a class EF2 inverter is used to generate HF AC in such a way that it can deliver power with variable loading condition while maintaining constant current (CC) or constant voltage (CV) according to the requirement of CC-CV charging profile. To supply power to this EF2 inverter, an AC-DC front-end converter (stage-1) is integrated with the charger. The stage-1 is operated as a constant voltage source to the EF2 inverter for CC mode and constant current source for CV mode operation. CC-CV at the battery end and PFC at the input end are achieved only by controlling the gate pulse of stage-1. The WPT coils are first simulated using Ansys Maxwell package, and the complete charger is simulated with PSIM simulation software. A scaled-down 200 W laboratory prototype of the proposed charger is developed and tested with a resistive load to validate the idea. The wireless power transfer is achieved for a maximum distance of 12 cm between the transmitting and receiving coil. Finally, the charger is tested to charge both 12 V and 24 V battery packs and the CC-CV charging profile is presented for the 24 V, 30 Ah battery pack.